BUSINESS FEASIBILITY STUDY OF FRUZFRUIT SORBETTO - Supriyatin, Yulinda; Sonny, Sonny (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
Following the pandemic that affected practically everyone in the world, includingIndonesia, the government recommended that people consume fruits more attentively asa self-protection strategy against the coronavirus. This is a healthy trend that mustcontinue to improve Indonesian nutrition. As a result, the author decided to launchFruzfruit Sorbetto, a frozen dessert sorbet business based on high-quality fresh fruits andmade from fruit raw materials, thus it has a considerably higher nutritional value and ishealthier. The goal is to give an alternate method to enjoy fruit. The Fruzfruit Sorbettocompany is expected to have a payback in year three and a total net present value (NPV)purchase of Rp. 218.265.256 in year five, with a sales ratio of 34%. Thus, FruzfruitSorbetto will constantly prioritize continual innovation and deliver the greatest serviceto provide a positive experience for every consumer.Keywords: Sorbet, fruit, business feasibility, business plan, healthy frozen dessert.